Comparative rhetorical analysis of Peter Obi and Bola Ahmed Tinubu's social media campaigns in the 2023 Nigerian presidential election - Precious Nwaoboli, Emeke; O. Uchenunu, Ambrose; S. Asemah, Ezekiel (Universitas Ahmad Dahlan, 2024)
The researchers carried out a comparative rhetorical analysis of Peter Obi (PO) and Bola Ahmed Tinubu's (BAT) social media campaigns during the 2023 Nigerian presidential election. Utilizing a qualitative textual analysis framework, the research focused on all campaign messages by Peter Obi and Bola Ahmed Tinubu (BAT) posted on Facebook and X (formerly Twitter) from September 28, 2022, to February 23, 2023, identifying a total of 223 messages, with 12 purposively selected for in-depth analysis. These texts were chosen for their representativeness of shared ideologies and their engagement potential, providing valuable insights into the candidates' communicative approaches. The study highlights the contrasting political ideologies embodied by Obi and Tinubu, as they emerged as frontrunners from the Labour Party and All Progressives Congress, respectively. Employing multiple coding techniques, the analysis categorized rhetorical elements, focusing on pathos, ethos, logos, call to action and themes of transparency and accountability, while also conducting sentiment analysis to classify the expressed sentiments. Findings reveal that Tinubu effectively leveraged a combination of logos, pathos, and ethos to establish credibility and connect with voters through logical policy proposals and emotional appeals, whereas Obi's campaign emphasized accountability, unity, and logical critique, resonating deeply with his audience through emotive language and local expressions. The researchers recommended that for political candidates prioritize emotional connections in their messaging. This study contributes to the existing body of knowledge by providing novel insights into the rhetorical strategies employed by political candidates in Nigeria, highlighting the significance of emotional connections and data-driven approaches in shaping electoral outcomes.